Exploring Creativity Drama in Literature English Learning Teaching of Islamic Boarding School - Nawangwulan, Septiyanisa Sekar; Putri, Ayunda Aliza; Anastasia, Dhea; Rohmana, Wahyu Indah Mala (Universitas Islam Negeri (UIN) Mataram, 2024)
This research explores the integration of drama creativity in English literature learning in the context of Islamic boarding schools, focusing on the experiences at Mambaus Sholihin Islamic boarding school in Gresik, East Java, Indonesia. The research uses descriptive qualitative methods to understand the implementation of literary literacy and drama, by examining the methods used by the source teachers. The findings of this study highlight the importance of drama in literature education, emphasizing its role in encouraging engagement, cultural exploration and moral development. The study features namely “Sky Theater” at Mambaus Sholihin boarding school as a practical example, demonstrating how drama contributes to a deep and diverse learning experience. The creative application of drama is not only as a tool to convey knowledge, as a means to convey religious and moral values. The teaching methods used, including drilling, memorizing, understanding and practicing, create a holistic learning environment that integrates technology and hands-on activities. This research underscores the transformative potential of drama in enriching English language education in boarding school emphasizing its role in nurturing individuals with essential life skills.